2005
DOI: 10.1080/03235400500094340
|View full text |Cite
|
Sign up to set email alerts
|

Biocides formulation of essential oils having antimicrobial activity

Abstract: Essential oils of fennel, peppermint, caraway, eucalyptus, geranium and lemon were tested for their antimicrobial activities against some plant pathogenic micro-organisms (Fusarium oxysporum, Alternaria alternate, Penicilium italicum Penicilium digitatum and Botyritus cinerea). Essential oils of fennel, peppermint, caraway were selected as an active ingredient for the formulation of biocides due to their efficiency in controlling the tested micro-organisms. Successful emulsifiable concentrates (biocides) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Previous studies were conducted to test the antimicrobial activities of essential oils of fennel, peppermint, caraway, eucalyptus, geranium and lemongrass against some plant pathogens including A. alternata (Abo-El-Seoud et al, 2005). The results of this study confirmed the antimicrobial activity of the essential oils against the fungus.…”
Section: Essential Oilssupporting
confidence: 73%
“…Previous studies were conducted to test the antimicrobial activities of essential oils of fennel, peppermint, caraway, eucalyptus, geranium and lemongrass against some plant pathogens including A. alternata (Abo-El-Seoud et al, 2005). The results of this study confirmed the antimicrobial activity of the essential oils against the fungus.…”
Section: Essential Oilssupporting
confidence: 73%
“…Different essential oils of plants have been shown to have an antimicrobial activity (Abo-El Seoud et al 2005; Bajpai et al 2009; Bakkali et al 2008; Khan and Ahmad 2011). In medicine, essential oils extracted from plants present antimicrobial activity against a range of bacteria including known antibiotic resistant strains (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In various industries, FAMEs are considered to be good adjuvants (Salimon et al 2012; Wang et al 2015), as well as effective solvents for EOs (Abo El-Seoud et al 2005). FAMEs are also important components of modern biodiesels (Giakoumis 2013).…”
mentioning
confidence: 99%